A CVD Method for Preparing CNTs-Grafted Carbon Fiber Fabrics under Quasi-Vacuum at Low Temperature. (13th March 2018) - Lu, Ruijiao; Wang, Chengguo; Wang, Yanxiang; Qin, Jianjie; Wang, Xinghui; Yao, Zhiqiang; Zheng, Linbao
Abstract : Carbon nanotubes (CNTs) were grown on the surface of carbon fiber fabrics by a novel chemical vapor deposition (CVD) with Co and Ni catalyst precursors loaded on their surfaces by impregnation respectively. The method is carried out at 600°C keeping the pressure at quasi-vacuum. It was found that when Co is used as catalyst and CVD time is 5 min, the yield of CNTs is moderate, the degree of graphitization is high and the tensile strength has the maximum value. The effect of parameters on the morphology and properties of CNTs-grafted carbon fiber fabrics has been revealed, which can serve as a fundamental engineering basis for exploring the optimized process. A damage and healing model of carbon crystals has been formulated to reveal the main reason that causes the variation in tensile strength of carbon fibers after the growth of CNTs, in which the reinforcing effect of CNTs is emphasized. Such results have provided the good foundation for the large-scale preparation of high-performance multi-scale reinforcements.